Coordination of contexts and taste disagreements - Bordonaba Plou, David (Daimon Revista Internacional de Filosofia, 2020)
In this paper, I will defend that there is an asymmetry between straightforwardly factual and non-straightforwardly factual disagreements (Field 2009) in terms of persistency and retraction, and that we can use what I will call coordination of contexts to explain these two asymmetries. To make my point I will focus on the kinematics of this type of disagreements. I will argue that one way to give a proper account of the kinematics of disagreements about taste and to discriminate between these two cases of disagreement is to focus on coordination of contexts.